Salinity Preference in Hatchery-Reared Juvenile Red Drum - Daryl C. Parkyn; Debra J. Murie; Edward T. Sherwood (The Scientific World Journal)
Juvenile red drum (Sciaenops ocellatus), reared in either 15- or 30-ppt salinity seawater, were tested to determine whether they develop preference for the salinity of the water in which they were cultured. In a two-choice test, large- and small-sized juvenile red drum chose the raceway that matched the seawater in which they were cultured over the other salinity. Additional large and small fish reared in either 15- or 30-ppt salinity water were also tested following a 4-h acclimation period that simulated the duration of transport time from the hatchery to a release site. These fish also showed preference for their original culture salinity. This observed salinity preference in juvenile red drum has implications with respect to movement or residency of hatchery-reared juvenile red drum out-planted into natural coastal systems.